Personal training - Ansell, Mark. (Exeter : Learning Matters, 2008)
A comprehensive, practical and genuinely reader-friendly introduction to personal training for today s students in UK.
Includes bibliographical references and index.
Keywords: Personal trainers; Physical education and training